Religion im Prozeß der Globalisierung - Beyer, Peter (Religion in der Gesellschaft, 2001)
The volume collects articles that present the current state of the English-language discussion on religion and globalization, especially from sociological and anthroplogical perspectives. A first section consists of theoretical contri-butions which inform the interpretations of the predominantly empirical studies that make up the second section. Overall, the selections show how the develop-ment of global society has contributed greatly to religious transformation; and how in various ways religion has been a significant force in the historical emergence of global society itself. - Content: Introduction, Peter Beyer: English-Language Views of the Role of Religion in Globalization; Section I: Theoretical Statements: Roland Robertson: The Globalization Paradigm: Thinking Globally; John W. Meyer, John Boli, George M. Thomas, and Francisco O. Ramirez: World Society and the Nation-State; Frank J. Lechner: Cultural Aspects of the World System; John H. Simpson: 'The Great Reversal': Selves, Communities, and the Global System; Arjun Appadurai: The Production of Locality; Peter Beyer: What Counts as Religion in Global Society? From Practice to Theory; Section II: Empirical Applications: Peggy Levitt: Local-Level Global Religion: The Case of United States - Dominican Migration; George Thomas: A World-Polity Interpretation of U.S. Religious Trends Since World War II; Rijk A. Van Dijk: From Camp to Encompassment: Discourses on Transsubjectivity in the Ghanian Pentecostal Diaspora; José Casanova: Globalizing Catholicism and the Return to a 'Universal Church'; William R. Garrett: Religion, Law, and the Human Condition; Peter Beyer: The Islamic Revolution in Iran